NRSF-GNAO1 Pathway Contributes to the Regulation of Cardiac Ca2+ Homeostasis. Issue 2 (21st January 2022) - Inazumi, Hideaki; Kuwahara, Koichiro; Nakagawa, Yasuaki; Kuwabara, Yoshihiro; Numaga-Tomita, Takuro; Kashihara, Toshihide; Nakada, Tsutomu; Kurebayashi, Nagomi; Oya, Miku; Nonaka, Miki; Sugihara, Masami; Kinoshita, Hideyuki; et al.
Abstract : Background: During the development of heart failure, a fetal cardiac gene program is reactivated and accelerates pathological cardiac remodeling. We previously reported that a transcriptional repressor, NRSF (neuron restrictive silencer factor), suppresses the fetal cardiac gene program, thereby maintaining cardiac integrity. The underlying molecular mechanisms remain to be determined, however. Methods: We aim to elucidate molecular mechanisms by which NRSF maintains normal cardiac function. We generated cardiac-specific NRSF knockout mice and analyzed cardiac gene expression profiles in those mice and mice cardiac-specifically expressing a dominant-negative NRSF mutant. Results: We found that cardiac expression of Gαo, an inhibitory G protein encoded in humans by GNAO1, is transcriptionally regulated by NRSF and is increased in the ventricles of several mouse models of heart failure. Genetic knockdown of Gnao1 ameliorated the cardiac dysfunction and prolonged survival rates in these mouse heart failure models. Conversely, cardiac-specific overexpression of GNAO1 in mice was sufficient to induce cardiac dysfunction. Mechanistically, we observed that increasing Gαo expression increased surface sarcolemmal L-type Ca 2+ channel activity, activated CaMKII (calcium/calmodulin-dependent kinase-II) signaling, and impaired Ca 2+ handling in ventricular myocytes, which led to cardiac dysfunction. Conclusions: These findings shed light on a novel function of Gαo in the regulation of cardiac Ca 2+ homeostasis and systolic function and suggest Gαo may be an effective therapeutic target for the treatment of heart failure. Abstract : Supplemental Digital Content is available in the text.